Effect of acute physical exercise on motor sequence memory - Blanca Marin Bosch; Bringard, Aurelien; Logrieco, Maria Grazia; Imobersteg, Nathalie; Lauer, Estelle; Thomas, Aurelien; Ferretti, Guido; Schwartz, Sophie; Igloi, Kinga (bioRxiv, 2020)
Recent studies suggest that acute physical exercise improves memory functions by increasing neural plasticity in the hippocampus. In animals, a single session of physical exercise has been shown to boost AEA (anandamide), an endocannabinoid known to promote hippocampal plasticity, which may in turn benefit hippocampal-dependent learning. Hippocampal neuronal networks do not only encode episodic memory representations, but also contribute to the sequential organization of memory elements, including motor sequences (Schendan et al., 2003; Eichenbaum, 2017). While previous work established that acute physical exercise has positive effects on declarative memory, whether it also influences memory for motor sequences remains unresolved. Here we studied the impact of moderate and high intensity acute physical exercise on motor sequence learning, and its underlying neurophysiological mechanisms in humans. To this end, we acquired behavioral, fMRI and AEA level data in fifteen healthy participants across three visits while they performed a serial reaction time task (SRTT) before and after a period of exercise (moderate or high intensity) or rest. We report that physical exercise increased AEA levels, and activity in the right hippocampus and caudate nucleus. Activity in both areas was directly linked to SRTT performance, which itself correlated with circulating AEA levels. These findings support that acute physical exercise favors hippocampal plasticity and potentially its broader role in memory function, including the consolidation of motor sequences.